Perilaku Konsumen dalam Keputusan Pembelian Tiwul Instan di Kabupaten Trenggalek - Pratiwi, Meihilda Dona; Agustina, Titin (Politeknik Negeri Lampung, 2024)
Indonesia has abundant natural resource potential, one of which is local non-rice food that can be processed by agro-industry and used by the community as an effort to diversify food. Instant tiwul is a processed product from cassava which is known to be used as an alternative food source of carbohydrates. Trenggalek Regency is the center of cassava production and the people have the habit of consuming instant tiwul. The price of instant tiwul is currently experiencing a more expensive price increase than rice because the raw materials are limited due to pest attacks and plant function change. This condition can affect product buying behavior, along with its role as an alternative food and increasingly selective consumers. His study was conducted to determine the process of instant tiwul purchase decisions, and factors that influence instant tiwul purchase decisions by end consumers in Trenggalek Regency. The research method used is descriptive analytical with data analysis methods in the form of descriptive analysis, and factor analysis. The results showed that the purchase decision process went through 5 (five) stages, namely need recognition, information search, alternative evaluation, purchase decision, and post-purchase evaluation. Five factors that influence the decision to purchase instant tiwul in Trenggalek Regency are first social factors in the form of variables of the influence of the surrounding environment and the influence of sellers, the second family factor includes variables of the number of family members and family income, the third personal factor is the variable of buyer age and occupation, the fourth is attractiveness in the form of packaging variables, ease of obtaining, and satiety endurance, and the five price and color factors include variable rice prices, instant tiwul prices, and colors.